The Effect of Active Knowledge Sharing Learning Strategy Assisted by Question Card on Concept Understanding of Excretory System Material and Student Communication Skills - Sukmawati, Danik Indah; Permadani, Karunia Galih; Prajoko, Setiyo Galih (BIOEDUKASI, 2024)
This research was motivated by the results of interviews with teachers, so far still using learning strategies that are unidirectional and not maximizing communication skills. The research method is quasi-experimental with the type of non equivalent control group design. This study aims to determine the effect of Active Knowledge Sharing learning strategy aided by question cards on concept understanding of excretory system material and communication skills. This research was conducted at SMA Muhammadiyah 1 Alternative Magelang City, using two classes. Based on the results of the study, with the application of Active Knowledge Sharing learning strategy aided by cards proved to have an effect. It can be proven in the results of hypothesis testing with Ancova which is sig. 0,000. Meanwhile, the use of Active Knowledge Sharing learning strategy with the help of question cards also affects students' communication skills. It can be proven in the results of hypothesis testing with Ancova which is sig. 0.000 where students have met the five indicators of communication skills. Both results show that the application of Active Knowledge Sharing learning strategy with question cards is better than the application of lecture learning method.